Modifying magnetic properties of MnBi with carbon: an experimental and theoretical study. (30th June 2022) - Kharel, Parashu; Lama, Bhubnesh; Flesche, Matthew; Mehlberg, Zachary; Lamsal, Buddhi; Valloppilly, Shah; Zhou, Yue; Sellmyer, David J; Paudel, Tula R
Abstract: MnBi and MnBi-based materials have been investigated as prospective rare-earth-free permanent magnets with moderate energy product. One of the main issues with MnBi synthesis is the presence of residual Bi in the sample which reduces the net magnetization. We have found that MnBi synthesized in the presence of carbon substantially reduces the amount of residual Bi, improving its saturation magnetization. We have synthesized Mn55 Bi45 and Mn55 Bi45 C x samples using arc melting and high-vacuum annealing. The room temperature x-ray diffraction patterns indicate that both Mn55 Bi45 and Mn55 Bi45 C x crystallize in the hexagonal NiAs-type structure. The Rietveld analysis of the x-ray patterns shows that the amount of residual Bi reduces from 16 wt.% for Mn55 Bi45 to 5 wt.% for Mn55 Bi45 Cx . The high-field (3 T) magnetizations measured at room temperature are 61 emu g −1 and 66 emu g −1 for Mn55 Bi45 and Mn55 Bi45 C x, respectively. To understand the role of C in enhancing the magnetization of MnBi, we carried out the first-principles calculations of both stoichiometric and nonstoichiometric MnBi alloys, which suggests that the increase of magnetization in Mn55 Bi45 C x may be due to the coating of MnBi grains with C.